Study on performance evaluation of service supply chain by extension method - Cheng, Jun (2021)
With the rapid development of the service industry, the service supply chain has become one of the most popular areas. With the logistics service supply chain being an important branch of the service supply chain, we should pay attention to the role of logistics service supply chain in enterprises. How to evaluate the logistics service supply chain comprehensively and rationally has become an important task for related enterprises to solve urgently. This paper, through extensive literature analysis and research on logistics service supply chain projects, established an indicator system composed of 18 secondary indicators from three perspectives of customer satisfaction, logistics service capabilities, and co-development ability, using the analytic hierarchy process (AHP) to determine the weight of each index and matter-element analysis to establish a logistics service supply chain performance evaluation model. At the end of the paper, the performance of S logistics enterprise is evaluated. The result turns out to be good, which is consistent with the actual situation, indicating that the evaluation system and method are effective and reliable.